Modeling Diet-Induced Obesity with Obesity-Prone Rats: Implications for Studies in Females - Giles, Erin D.; Jackman, Matthew R.; MacLean, Paul S. (Frontiers in Nutrition, 2016)
Obesity is a worldwide epidemic, and the comorbidities associated with obesity are numerous. Over the last two decades, we and others have employed an outbred rat model to study the development and persistence of obesity, as well as the metabolic complications that accompany excess weight. In this review, we summarize the strengths and limitations of this model and how it has been applied to further our understanding of human physiology in the context of weight loss and weight regain. We also discuss how the approach has been adapted over time for studies in females and female-specific physiological conditions, such as menopause and breast cancer. As excess weight and the accompanying metabolic complications have become common place in our society, we expect that this model will continue to provide a valuable translational tool to establish physiological relevant connections to the basic science studies of obesity and body weight regulation.